Significance of serum ferritin and De Ritis ratio in non-alcoholic fatty liver disease as diagnostic markers - Anoshia Javed; Dr. Khadija Mehboob; Amir Rashid; Asifa Majeed; Muhammad Imran Ibrahim; Dr. Iffat Mushtaq (Journal of the Pakistan Medical Association, 2024)
Objective: To ascertain the significance of serum ferritin and De Ritis ratio as diagnostic markers in patients of non-alcoholic fatty liver disease with and without type 2 diabetes mellitus. Methods: The comparative cross-sectional study was conducted from February to October 2022 at the Radiology Department of Combined Military Hospital, Rawalpindi, Pakistan, and comprised individuals aged 30-65 who were divided into 3 groups. Healthy controls formed group I, non-alcoholic fatty liver disease patients without type 2 diabetes mellitus formed group II and non-alcoholic fatty liver disease patients with type 2 diabetes mellitus were in group III. Blood 5ml was withdrawn and assessed for alkaline phosphatase, aspartate transaminase, alanine transaminase and ferritin. De Ritis ratio was calculated and subjected to intergroup comparison. Data was analysed using SPSS 22. Results: Of the 210 subjects, 110(52.4%) were males and 100(47.6%) were females, with 70(33.3%) in each of the three groups. Group I had 38(54.3%) females and 32(45.7%) males with mean age 37.50±4.513. In group II, there were 27(38.6%) females and 43(61.4%) males with mean age 45.86±9.646, while in group III there were 35(50%) females and 35(50%) males with mean age 54.01±9.243. Serum ferritin levels were significantly increased in patient groups II and III compared to control group I (p<0.05). De Ritis ratio was markedly raised in groups II and III compared to group I (p<0.05). Ferritin was significantly correlated to age, weight, height, fasting blood sugar, haemoglobin, alkaline phosphatase, aspartate aminotransferase, alanine transaminase and bilirubin (p<0.05). De Ritis ratio had a significant correlation with body mass index and fasting blood sugar (p<0.05). Conclusion: Serum ferritin and De Ritis ratio were found to be useful diagnostic indicators for non-alcoholic fatty liver disease, highlighting their importance in improving disease screening. Key Words: NAFLD, Non-alcoholic steatohepatitis, Ferritin, SGPT, SGOT.